Usando as regras de produtos notáveis, calcule:
A) (√3+√6)2
B) (2√5+3).(2√5-3)
C) (√2-√6)²
D) (2√2+4).(2√2-4)
Respostas
respondido por:
2
A) (√3+√6)² =
(√3)² + 2√3√6 + (√6)² = 3+6√2+6 = 9+6√2
B) (2√5+3).(2√5-3)
(2√5)² - 3² => 4.5-9=> 20-9=> 11
C) (√2-√6)²
(√2)²- 2√2√6 + (√6)²
2- 4√3 + 6 => 8 - 4√3
D) (2√2+4).(2√2-4)
(2√2)² - 4² => 4.2 -16 => 8-16 => 8
(√3)² + 2√3√6 + (√6)² = 3+6√2+6 = 9+6√2
B) (2√5+3).(2√5-3)
(2√5)² - 3² => 4.5-9=> 20-9=> 11
C) (√2-√6)²
(√2)²- 2√2√6 + (√6)²
2- 4√3 + 6 => 8 - 4√3
D) (2√2+4).(2√2-4)
(2√2)² - 4² => 4.2 -16 => 8-16 => 8
Perguntas similares
7 anos atrás
7 anos atrás
7 anos atrás
10 anos atrás
10 anos atrás
10 anos atrás